2018
DOI: 10.1089/vim.2017.0201
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle Release from Cell Lines and Its Anti-Influenza Activity

Abstract: Microparticles (MPs) are vesicles that are released by budding from plasma membrane of living cells. Recently, the role of MPs in antiviral activity has been proposed. We investigated quantity and anti-influenza activity of MPs from human alveolar epithelial cells A549, human bronchial epithelial cells BEAS-2B, human colon adenocarcinoma cells HT-29, and the human lung fibroblast cells MRC-5. MPs were found from all four cell lines. However, anti-influenza activity against an H1N1 influenza virus was found onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…It is highly desired to achieve a sharp contrast of labelling and low background for a better diagnosis in a clinical setting. A close assessment of the SNA staining histogram for both cells is found to be a heterogeneous labelling pattern, which is consistent with earlier report 70 . However, P4 showed comparatively less heterogeneous labelling to both cell lines, especially for A549.…”
Section: Discussionsupporting
confidence: 92%
“…It is highly desired to achieve a sharp contrast of labelling and low background for a better diagnosis in a clinical setting. A close assessment of the SNA staining histogram for both cells is found to be a heterogeneous labelling pattern, which is consistent with earlier report 70 . However, P4 showed comparatively less heterogeneous labelling to both cell lines, especially for A549.…”
Section: Discussionsupporting
confidence: 92%
“…It is unclear, what function then EV-based tetraspanins might have in the context of viral infection, and it might be speculated that cells use EVs to titrate away virus into membrane structures that are unable to provide replication and protein synthesis machineries for the virus. This is supported by the findings that EVs might have anti-influenza infection activity in vitro [73].…”
Section: Tetraspanins In Pathogen Infectionmentioning
confidence: 58%
“…Our findings support a novel model of VZV vasculopathy pathogenesis, with adventitial fibroblast transformation to myofibroblasts contributing to arterial remodeling by proliferation and migration and further adventitial cell-to-cell viral dissemination and endothelial activation mediated by VZV-MPs. MPs are important intercellular signaling mediators, 3,7 but few studies have demonstrated their role as mediators of infectious propagation. 8 Viral proteins detected in MPs could facilitate interaction on host cells and may also regulate tropism.…”
Section: Discussionmentioning
confidence: 99%